Pengembangan Modul Ajar P5 Menggunakan Model Pembelajaran Discovery Learning Berbasis Media Pembelajaran IT di SD - Irmawati M; Dita Mulyana Ramadhani; Muflihah Baktiar; Muhammad Adnan; Kafrawi Kafrawi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The development of P5 teaching module in the curriculum independent is very important because it adapts to technological developments and the transition from the previous 2013 curriculum to the independent curriculum. The current problem in the school is that teachers are still having problems in compiling teaching modules and the lack of use the interactive learning models also the use of IT-based learning media so it takes an impact on achieving learning objectives namely low student learning outcomes. Developing a teaching module requires a model that can involve students in the learning process also the use of IT-based learning media that can adapt to technological developments and the needs of the times. So, the aim of this research is to determine the validity of modules, IT-based learning media with research instruments, also to determine the responses of teachers and students in using teaching modules. What will be measured in the development of this module are the validity of the module, learning media, research instruments also the student and teacher responses in using the module. This research is development research that using the 4-D model, namely define, design, develop and disseminate. The instruments used are validation sheets, student-teacher response sheets, and student learning result test sheets. According to the study results, it was found that the validity of teaching modules, IT-based learning media and research instruments is absolutely valid category so it can be applied in the learning process. Meanwhile, the response of the students and the teachers about using teaching module is get a very positive response.